THE ROLE OF THINKING STYLES AS MEDIATORS BETWEEN PERMISSIVE PARENTING STYLES AND CAREER DECISION SELF-EFFICACY OF INDONESIAN GEN Z YOUTHS - Situmorang, Dominikus David Biondi; Salim, Rose Mini Agoes (International Journal of Psychosocial Rehabilitation, 2020)
Career decision self-efficacy (CDSE), which alludes to an individual’s capacity to effectively make imperative career-related choices, is emphatically affected by two components: parenting styles and thinking styles. Hence, this non-experimental quantitative consider analyzes the effects of parenting styles and thinking styles on the CDSE of gen Z youths. The members comprised of 617 gen Z students (11th and 12th grades) from three driving schools in Jakarta, Indonesia, whereas the measuring disobedient included the Career Decision Self-Efficacy Scale – Short Form, the Parental Authority Questionnaire, and the Thinking and Styles Inventory - Revised II. Based on the discoveries, CDSE was altogether affected by the permissive parenting styles as well as the Type I, Type II, and Type III Thinking Styles. Besides, the intervention investigation found that the thinking style intervened the relationship between the permissive parenting styles and CDSE.